Manganese(III) Complexes with Tetradentate Schiff Base Ligands: IR, UV/Vis, Electrochemistry and Fluorescence Properties - Naser Eltaher Eltayeb (Universitas Gadjah Mada, 2020)
Three trivalent manganese complexes have been synthesized, isolated, and characterized, namely, [MnCl(OH2)(Lx)].nH2O (I-III). Lx is a tetradentate Shiff base ligand, where Lx = LI, 2,2'-1,2-phenylenebis [nitrilomethylylidene]bis(phenolate), LII, 2,2'-1,2-phenylenebis[nitrilomethylylidene]bis(5-methoxyphenolate), and LIII, 2,2'-1,2-phenylenebis[nitrilomethylylidene]bis(4-methoxyphenolate), n = 1, 1.5 and 0 for I, II and III, respectively. These complexes were characterized using IR, elemental analysis and UV-Vis spectroscopy. In addition, the fluorescence, photoluminescence (PL), electrochemistry and thermal stability of these complexes were studied.